Node characteristics based LR-WPAN routing algorithm research for network energy optimization - QIAN Zhi-hong; ZHANG Xiao-fan; WANG Yi-jun; GUAN Ting-yan (Tongxin xuebao)
An enhanced algorithm named F-ZBR was proposed considering the weakness of ZigBee hybrid routing algorithms and the energy consumption in LR-WPAN network.The proposed scheme reduced overall energy consumption of network by the definition of minimum routing energy and controlling the direction of RREQ packet as well as the number of hop,besides the introduction of energy flag in RREQ packet.The analysis on simulation result indicated that F-ZBR performs significantly better than ZBR in packet delivery ratio,available nodes ratio as well as remaining energy ratio.By the algorithm,therefore,it may be depleted that huge data transmission gives rise to over-consuming energy of RN+ nodes or even collapse in ZigBee network.And the algorithm also prolongs the life span of network.